2008
DOI: 10.1016/j.marpolbul.2008.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of tributyltin by tributyltin resistant marine Pseudoalteromonas sp. cells

Abstract: The isolate, Pesudoalteromonas sp. TBT1, could grow to overcome the toxicity of tributyltin chloride (TBTCl) up to 30 microM in the absence of Cl(-) in the medium until the cells reached an exponential phase of growth. The viability, however, was reduced after the cells reached a stationary phase. The degradation products, such as dibutyltin (DBT) and monobutyltin (MBT), were not detected in the growth medium, indicating that the isolate has no ability to degrade TBT into less toxic DBT and MBT. Up to about 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Adsorption of TBT molecules is an important function of cell walls for Pseudoalteromonas sp. to prevent the inflow of molecules into the cytoplasm Kubota et al, 2004;Mimura et al, 2008a;Mimura et al, 2008b . Recently, a TBT-degrading Aeromonas veronii, which uses TBT as a carbon source, was isolated from an estuarine environment Cruz et al, 2007 .…”
Section: Enumeration Of Colony-forming Cells After Exposure To Tbtmentioning
confidence: 99%
See 1 more Smart Citation
“…Adsorption of TBT molecules is an important function of cell walls for Pseudoalteromonas sp. to prevent the inflow of molecules into the cytoplasm Kubota et al, 2004;Mimura et al, 2008a;Mimura et al, 2008b . Recently, a TBT-degrading Aeromonas veronii, which uses TBT as a carbon source, was isolated from an estuarine environment Cruz et al, 2007 .…”
Section: Enumeration Of Colony-forming Cells After Exposure To Tbtmentioning
confidence: 99%
“…We have pointed out previously that the cell wall of a marine Pseudoalteromonas sp. plays an important role in preventing the inflow of TBT molecules into the cytoplasm across the membrane Kubota et al, 2004;Mimura et al, 2008a;Mimura et al, 2008b . The isolate, Photobacterium sp.…”
Section: Capacity Of Adsorption Of Tbt Molecules As An Indicator Of Tmentioning
confidence: 99%
“…While inorganic forms of tin are regarded as non-toxic, these more lipid-soluble organotins can be highly toxic (Gadd, 2000). They are the main active ingredients in pesticides used to control a broad spectrum of organisms as they act as biocides for fungi, bacteria and insects (Mimura et al, 2008;Fent, 2006). Nevertheless, research undertaken since the early 1970s has shown that TBT is highly toxic to a larger number of non target aquatic organisms (Antizar-Ladislao, 2008).…”
Section: Tributyltinmentioning
confidence: 99%
“…Nevertheless, research undertaken since the early 1970s has shown that TBT is highly toxic to a larger number of non target aquatic organisms (Antizar-Ladislao, 2008). TBTs' properties were recognized in the 1950s and since then this compound has been extensively used for various industrial purposes such as slime control in paper, as a wood preservative, as a polyvinyl chloride (PVC) stabilizer, and as fungicide in agriculture (Mimura et al, 2008). In the 1970s, TBT paints widely replaced copper-based paints due to their superior performance in terms of efficacy and duration (Sonak, 2009).…”
Section: Tributyltinmentioning
confidence: 99%
“…Some microorganisms are able to resist/degrade TBT (Cruz et al, 2007;Mimura et al, 2008;Suzuki and Fukagawa, 1995), this being a phenomenon of relevance to the environmental cycling of this compound. Considering TBT tolerance/resistance of bacteria, various possible mechanisms have been proposed: (i) TBT efflux systems Hernould et al, 2008;Jude et al, 2004); ii) transformation into less toxic compounds (dibutyltin, DBT and monobutyltin, MBT) by biotic and abiotic factors (Cruz et al, 2007;Pain and Cooney, 1998); (iii) degradation/metabolic utilization as a carbon source (Cruz et al, 2007;Kawai et al, 1998) and (iv) bioaccumulation into the cell without breakdown of the compound (Dubey and Roy, 2003).…”
mentioning
confidence: 99%